2023
DOI: 10.1186/s12968-023-00944-x
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of cardiac magnetic resonance feature tracking parameters for the evaluation of the arrhythmic risk in patients with mitral valve prolapse

Abstract: Objectives The identification of patients with mitral valve prolapse (MVP) presenting high arrhythmic risk remains challenging. Cardiovascular Magnetic Resonance (CMR) feature tracking (FT) may improve risk stratification. We analyzed the role of CMR-FT parameters in relation to the incidence of complex ventricular arrhythmias (cVA) in patients with MVP and mitral annular disjunction (MAD). Methods 42 patients with MVP and MAD who underwent 1.5 T C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 26 Implementing T1-mapping and CMR feature tracking could reveal sub-clinical abnormalities in IVF patients with inferolateral MAD that might correlate with arrhythmias. 25 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Implementing T1-mapping and CMR feature tracking could reveal sub-clinical abnormalities in IVF patients with inferolateral MAD that might correlate with arrhythmias. 25 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) imaging has good spatial and tissue resolution. It can provide information on cardiac function, morphology, hemodynamics, and myocardial tissue characteristics, especially for CMR feature tracking technology, which can detect subtle cardiac morphological and functional changes early [ 13 , 14 ]. A previous study has reported the effect of MetS on LV structure and function by CMR feature tracking [ 15 ].…”
Section: Introductionmentioning
confidence: 99%